Kontroversi Putusan Hukum Tentang Royalti Hak Cipta Lagu Sebagai Harta Bersama - Septiani, Dini Lionita; Setiawan, Wahyu; Oktora, Nency Dela; Angkasa, Nawa; Fernando, Henky (Al-Mizan (e-Journal), 2025)
The controversy over legal decisions regarding song copyright royalties as joint property in Indonesia can generally be termed joint ownership of individual rights. This paradigm assesses the status of joint property based on the time of acquisition, the spouse's contribution, or the character of the asset. Joint property in Indonesian marital law is all property acquired during the marriage period unless there is a property separation agreement agreed upon before marriage. Inherited assets, inheritance, or grants remain the personal property of each spouse unless otherwise agreed. This issue arises because royalties have both a personal nature and long-term economic potential. This article analyses the controversy using a qualitative approach with a case study method, exploring the forms of controversy, causal factors, and implications. Data were obtained from a qualitative case study conducted by reviewing decision No. 1622/Pdt.G/2023/PA.JB and interviewing 3 judges and 2 advocates. The main findings show that controversy arose in three aspects: royalty division, copyright status, and asset division. Contributing factors include the misalignment between the personal nature of copyright and the communal concept of property, legal uncertainty, and the difficulty of economic valuation of song copyrights. The implications of this controversy include shifting social norms, uncertainty for creators, and increased complexity in asset division. This research underscores the need for comprehensive legal reform to accommodate the complexity of copyright royalty issues in the context of common property, as well as the development of more accurate valuation methods. This study contributes to a deeper understanding of the interaction between intellectual property law and family law in Indonesia.